Treatment and Management of Diarrhea in Children: A Literature Review - Reihana Ramadlani Ibna; Helda (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
ABSTRACT Background: Diarrhea is an endemic disease in Indonesia and also a potential Extraordinary Event (KLB) disease which is often associated with death. Therefore, a literature review regarding the management and management of diarrhea in children is needed to improve the quality of health services. Method: PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) is used in writing literature reviews. Using the Sciendirect, Scopus and Pubmed databases covering the years 2011-2022. Results: From several journal searches with the keywords diarrhea, diarrhea management, diarrhea management which were filtered again according to predetermined criteria in the 2011-2022 time period, 9 suitable journals were obtained. These journals discuss five main topics according to the principles of management and management of diarrhea, namely the Ministry of Health's LINTAS Diarrhea program (Five Steps to Overcoming Diarrhea). Conclusion: Management of diarrhea in accordance with recommendations from the Ministry of Health of the Republic of Indonesia and WHO will improve the quality of good services. Keywords : Diarrhea, The Treatment of Diarrhea, Management of Diarrhea.